Impact of age on survival of patients with out‐of‐hospital cardiac arrest transported to tertiary emergency medical institutions in Osaka, Japan. Issue 11 (17th October 2019) - Nakamura, Fumiko; Kajino, Kentaro; Kitamura, Tetsuhisa; Daya, Mohamud R; Ong, Marcus EH; Matsuyama, Tasuku; Yamada, Tomoki; Hayakawa, Koichi; Irisawa, Taro; Yoshiya, Kazuhisa; Noguchi, Kazuo; Nishimura, Tetsuro; et al.
Abstract : Aim: The purpose of this study was to evaluate the out‐of‐hospital cardiac arrest (OHCA) characteristics of patients stratified by age who had resuscitation attempted and were transported to tertiary emergency medical institutions in Osaka Prefecture, Japan; especially those of advanced age. Methods: A prospective, population‐based, observational review was carried out of consecutive OHCA patients with emergency responder resuscitation attempts from July 2012 to December 2016 in Osaka, Japan. Patients were classified into four groups: (i) 18–64 years; (ii) 65–74 years; (iii) 75–84 years; and (iv) ≥85 years. Patient, event and treatment characteristics were examined for patients with presumed cardiac etiology of OHCA. The primary outcome was the 1‐month survival with a neurologically favorable outcome. Results: A total of 4636 patients with OHCA of presumed cardiac origin were transported to tertiary emergency medical institutions. The number of patients in the four groups was as follows: (i) 1290 (27.8%); (ii) 1102 (23.8%); (iii) 1420 (30.6%); and (iv) 824 (17.8%). The 1‐month survival with a neurologically favorable outcome was: (i) 207 (16.0%); (ii) 96 (8.7%); (iii) 60 (4.2%); and (iv) seven (0.85%). In a multivariate analysis for 1‐month survival with a neurologically favorable outcome, increased age was a significant prognostic factor (≥85 years; adjusted odds ratio 0.08, 95% confidence interval 0.03–0.23) for poor outcomes. Conclusions: In this population, advanced age (≥85 years) was strongly associated with poor outcomes. Further discussion of policies directed at resuscitation of very elderly OHCA patients is required, considering limited medical resources and the rapidly aging population in Japan. Geriatr Gerontol Int 2019; 19: 1088–1095 .